Learning Activity as a Means of Developing Theoretical Thinking Capacities - Clarindo, Cleber Barbosa da Silva; Miller, Stella; Kohle, Érika Christina (Frontiers in Psychology, 2020)
The main purpose of this article is to discuss the development of capacities linked to theoretical thinking during the formation process of Learning Activity in students of the early years of elementary school. It brings some elements for consideration which could form the basis for thinking about teaching activity as a means of conducting them to that development. It starts from the hypothesis that the development of the capacities of analysis, reflection and mental planning depends, essentially, on the systematic organization of the principles and ways of action of the students on the theoretical contents in their learning process. And also that Learning Activity is the most appropriate form of organization of the pedagogical work for the development of those methods of action that enable students to appropriate what is the most elaborated in human culture. With that, the students achieve new higher psychological formations and a new way of thinking and acting in the environment. The theoretical study, carried out through locating, gathering, analyzing, synthesizing and reframing the theorical ideas contained in publications, texts, articles and books by authors of the Cultural-Historical Theory. The study gives emphasis to Learning Activity as an adequate way for the development of psychic neoformations of school-age children, since their organization, based on the solution of learning tasks through learning actions, is the source of the development of analysis, reflection and mental planning skills, as constituent parts of theoretical thinking in school-age children.